Microwave generation in synchronized semiconductor superlattices - Gaifullin, M.B.; Alexeeva, N.V.; Hramov, A.E.; Makarov, V.V.; Maksimenko, V.A.; Koronovskii, A.A.; Greenaway, M.T.; Fromhold, T.M.; Patanè, Amalia; Mellor, Christopher J.; Kusmartsev, F.V.; Balanov, A.G. (American Physical Society, 2017)
We study high-frequency generation in a system of electromagnetically coupled semiconductor superlattices fabricated on the same doped substrate. Applying a bias voltage to a single superlattice generates high-frequency current oscillations. We demonstrate that within a certain range of the applied voltage, the current oscillations within the superlattices can be self-synchronized, which leads to a dramatic rise in the generated microwave power. These results, which are in good agreement with our numerical model, open a promising practical route towards the design of high-power miniature microwave generators.